Identifikasi Kemampuan Berpikir Logis Mahasiswa Calon Guru Fisika Menggunakan Instrument TOLT - Rahmawati Rahmawati; Edy Kurniawan; A. Muafiah Nur (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
This study aimed to identify the type of reasoning and the level of prospective physics teacher studentsÃ¢â¬â¢ logical thinking ability. This type of research was a field study with a quantitative descriptive method. The test was the technique used in collecting data of this study. The instrument used in this study was the standard test like Test of Logical Thinking (TOLT). This test consists of 10 questions that measured five types of reasoning, namely proportional reasoning, variable control, probabilistic reasoning, correlation reasoning, and combination reasoning. The level of logical thinking ability was distinguished into concrete, transitional, and formal thinking operational. The sample of this study was students of physics teacher candidates at the first-year level, totaling 30 students. ÃÂ All of data was analyzed by quantitative descriptive. In general, students tend to the type of proportional reasoning and controlling variables and less on probabilistic reasoning. Based on the level of logical thinking ability, the results showed that the percentage of 30 students who were in the concrete, transitional, and formal categories, respectively, were 30%, 30%, and 60%. This data becomes the basis for consideration in the development of learning models and learning assessments used in lectures, especially in Department of Physics Education in one of the University in Makassar city, so that they are able to contribute to the development of students' level of logical thinking skills as a provision for the next life.